Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/min10070627
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Geochemical Characteristics of Lithium and Rare Earth Elements in High-Sulfur Coal from the Donggou Mine, Chongqing, Southwestern China

Abstract: Coal and coal by-products are considered as the potential raw materials for critical elements (e.g., rare earth elements, Li, Ga, Ge, etc.), which have attracted much attention in recent years. The purpose of this study is to investigate the mineralogical and geochemical characteristics, and controlling geological factors of lithium and rare earth elements in the Lopingian (Wujiaping Formation) coal from the Donggou Mine, southeastern Chongqing Coalfield, China. Results indicate that lithium and rare earth ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
4
12
0
Order By: Relevance
“…The subhedral and colloidal anatase and fracture-filling apatite also suggest a hydrothermal origin. Rhabdophane, a secondary mineral containing REY, is rare in coal but is not uncommon in late Permian coals from southwestern China and considered as a product in relation to the hydrothermal origin. , Rhabdophane was confirmed in the roof, coal, and floor samples and occured in the granular form in the matrix of NH 4 -illite (Figure A–F), indicating a hydrothermal origin.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The subhedral and colloidal anatase and fracture-filling apatite also suggest a hydrothermal origin. Rhabdophane, a secondary mineral containing REY, is rare in coal but is not uncommon in late Permian coals from southwestern China and considered as a product in relation to the hydrothermal origin. , Rhabdophane was confirmed in the roof, coal, and floor samples and occured in the granular form in the matrix of NH 4 -illite (Figure A–F), indicating a hydrothermal origin.…”
Section: Discussionmentioning
confidence: 98%
“… 62 If the UCC-normalized Eu anomaly occurs positive or negative in coals, it is suggested that the inorganic materials derived from mafic or felsic compositions, respectively. 62 The Eu anomaly has been used in the Huayingshan, 71 Nantong, 50 and southeastern Chongqing Coalfields 34 for indicative of the sediment source region being not the mafic basalts of the Kangdian Upland. The REY distribution patterns indicate that the inorganic material of the Xingying coals is from the mafic basalts of the Kangdian Upland, owing to the significant positive Eu anomalies, which further confirmed the results mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would offer the potential to reduce our dependence on other countries for these critical materials and also create new industries in regions where coal has played an important economic role. Zou et al (2020) carried out a detailed study to understand the controlling geological factors for the enrichment of not only REE but also another demanding element, Li, in coal from the Donggou Mine (southeastern Chongqing Coalfield, China). The possible recovery of REE from abundant coal and coal ash is an exciting new research area, representing a dramatic paradigm shift for coal, innovations to REE manufacturing and bypass mining.…”
Section: Ree In Coal and Coal Fly Ashmentioning
confidence: 99%